Io faccio nuove tutte le cose.: Una rilettura della Passione di Cristo (PHILM. Rivista di filosofia e cinema, 2024)
The figure of Christ has been the subject of investigation by numerous filmmakers and their audiences for its historical and symbolic value. At the beginning of the 21st century, the controversial film The Passion of the Christ (Gibson, 2004) represented a shift towards a more religious approach to the figure of Christ. The essay examines the role of montage in the film, illustrating how it generates specific interpretations for an audience already familiar with the spiritual import of the Gospel narratives. It presents a theological discourse that engages with the viewer’s existing faith.